PS2-15: Racial Disparities in Biobank Participation among Men in Southern California - Koebnick, Corinna (Clin Med Res, 2014)
BACKGROUND/AIMS: Previous research suggests that participation of men in research is particularly low. We sought to identify predictors of participation among men in different racial groups in order to optimize future recruitment strategies. METHODS: We assessed predictors of participation on randomly selected Kaiser Permanente Southern California male members = 18 years of age (n = 90,199) between November 2012 and June 2013. Men were asked to provide saliva samples for a research biobank. Potential predictors of participation were age, long-term membership (= 5 years), no significant gaps in health care coverage (<3 month in last 3 years), physical examination within the last 3 years and neighborhood education and income. RESULTS: Overall participation among men was 4.4%. Restricting recruitment to men with at least 5 years of membership, no significant gaps in health care coverage, and at least one physical examination, improved participation from 5.3% to 10.6% in Whites, and from 1.0 % to 2.7% in Hispanics but only modestly in Blacks from 1.5% to 2.3%. In logistic regression models predicting participation, the most important predictors of participation were having at least one physical examination (OR 1.46, 95%-CI 1.34–1.59) in Whites and long-term membership in Hispanics (OR 1.38, 95%-CI 1.11–1.69). None of the restrictions significantly predicted participation in Blacks (p for interaction with race <0.001). CONCLUSIONS: The application of restrictions based on longer membership and regular physical examinations may increase recruitment of non-Hispanic White and Hispanic men for biobank participation.